Willingness to seek medical care for tuberculosis and associated factors among the elderly population in Shenzhen: a cross-sectional study - Qing Yuan; Yi Zhu; Zuxun Lu; Xiaojun Wang; Yong Gan; Xin Shen; Yanfang Guo; Jing Feng; Yunxia Wang; Juanjuan Zhang; Zihui Lei; Xin Meng; et al. (BMJ Open)
Objectives This study was aimed to assess the willingness of elderly people to seek medical care for tuberculosis (TB) and the associated influencing factors.Design A cross-sectional study.Setting A multistage random survey was conducted in Bao’an District of Shenzhen in China.Participants A total of 1200 elderly people aged 65 or above were recruited for the study and completed a structured questionnaire between September and October 2019.Main outcome measures Descriptive and binary logistic stepwise regression analyses were conducted to analyse the characteristics of elderly individuals, their willingness to seek medical care for TB and associated factors.Results Among the final 1123 respondents, 943 (84.0%) were willing to seek medical care if they discovered suspicious TB symptoms. Binary logistic stepwise regression analysis indicated that respondents whose family annual income per capita was 50 000–100 000¥ (OR=2.56, 95% CI: 1.44 to 4.54, p<0.01) and who had positive attitudes (≥3 scores: OR=3.10, 95% CI: 1.90 to 5.05, p<0.01) or practices (≥4 scores: OR=3.13, 95% CI: 1.82 to 5.39, p<0.01) towards TB were more willing to seek medical care for TB.Conclusions Willingness to seek medical care for TB in the elderly population can be improved according to the determinants.